Analysis of processes and costs of alternative packaging options of sterile goods in hospitals: A case study in two German hospitals - Markus Krohn; Josefine Fengler; Thomas Mickley; Steffen Fleßa (Health Economics Review, 2019)
Background: Hospitals should monitor the costs of all direct and indirect processes in order to achieve efficiency and safeguard financial sustainability. One neglected process with significant costs is the processing of reusable medical devices and their packaging performed in the central sterilisation supply department and the operating room. The objective of this research is to analyse and compare processes and costs of four different packing alternatives, i.e. non-woven sterilisation wrap with two sheets, one-step wrap, sterilisation container with inner wrap and sterilisation container without inner wrap. Methods: We defined sub-processes that are directly related to the packaging options and measured them through a comprehensive time study. For all sub-processes and the total processes a distribution fitting and a Monte-Carlo-Simulation were performed. We calculated the costs for all sub-processes, i.e., costs for personnel, variable costs and the respective share of fixed and jump-fixed costs (e.g. depreciation of containers) associated with each packaging option. All results are discussed through various scenarios to evaluate the advantageousness of all packaging options. Results: The four packaging options are associated with different costs. 'Sterile container without inner wrap' causes 2.05 exteuro per use. The options 'sterile container with inner wrap' (3.24 exteuro), 'one-step sterilisation wrap' (3.44 exteuro) and 'two sheets sterilisation wrap' (3.87 exteuro) cause higher costs. With regard to personnel costs the option 'sterile container without inner wrap' clearly causes the lowest costs. In addition, variable costs are lower in case of sterile container. Sterile container only cause higher costs in the aspect of fixed and jump-fixed costs per packaging. Conclusions: The analysis shows that even under a broad set of scenarios the 'sterile container without inner wrap' is the most cost-effective alternative. The evaluation of the options 'sterile container with inner wrap' and 'one-step sterilisation wrap' remains particularly interesting as they often yield comparable results. Both options cause approximately the same personnel costs, so the decision appears to be more dependent on the material prices for wrap or the frequency and duration of use for container. It turns out that the personnel time and consequently the personnel costs significantly influence the rational choice of the packaging options.
Keywords: 330; Non-woven sterilisation wrap; Sterilisation container; Process analysis; Cost analysis; Time study; CSSD; OR; Monte-Carlo-simulation